Implementation of the AKSYON Fund under Department Order No. 04 (2023): Evidence of a Governance Gap in Labor Migration Policy for Overseas Filipino Workers in Saudi Arabia - Arca, Emil (Future Science, 2026)
The implementation of the AKSYON Fund (Department Order No. 04, Series of 2023), identifies governance gaps in labor migration policies affecting Overseas Filipino Workers (OFWs) in Saudi Arabia. Employing a mixed-methods design, the research integrates quantitative data from 200 respondents—including migrant workers and diplomatic staff—with qualitative insights from in-depth interviews with documented and undocumented OFWs. The results show that core services like legal, medical, repatriation, financial help, shipping of remains, and rescue operations are generally helpful, but they are not as effective as they could be because of delays in operations, complicated procedures, and limited access. Statistical analysis reveals a significant disconnect between institutional assessments and migrant experiences, highlighting a critical gap in policy implementation. Qualitative evidence further underscores pervasive vulnerabilities, with 100% of respondents reporting financial risk and a majority facing social, health, and psychological challenges. Drawing on Strategic Action Fields and Recognition Theory, the study argues that these gaps reflect a misalignment between institutional policy design and the lived realities of migrants. The research contributes to migration governance literature by advocating for a shift from mere policy provision toward a performance-oriented, migrant-centered delivery system.